(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aim of the present investigation is to study the Emotional Intelligence and Self Concept of school students of Amritsar district. The sample for the study consisted of 400 IX grade students of government and private schools. The participants were assessed with Saraswat Self concept scale (2005) and Mangal and Mangal Emotional Intelligence scale (2002).t-test and ANOVAwere used to analyze the data. The study revealed that Students of private schools have better self conceptso they have higher emotional intelligence as compared to students of government schools. It is also found that girls have better self concept as compared to the boys. Based on the findings it is suggested that the teachers, parents and the friends have to take necessary steps to promote better emotional intelligence and inculcate high self concept among the students. It is also suggested that parents and teachers should equally involve boys in the different activities so that self concept of boys can also be improved.